Formulasi dan Uji Mutu Fisik Sediaan Cream Blush Ekstrak Buah Naga Merah (Hylocereus costaricensis) Dengan Variasi Konsentrasi Beeswax - Ni Nyoman Yudianti Mendra; Komang Priskila Adelia Silvy; I Made Agus Sunadi Putra (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2026)
The use of natural colorants derived from natural sources, such as red dragon fruit (Hylocereus costaricensis), can be applied in cosmetic formulations including blush in, lipstick, eyeshadow, and others. Blush on has several consistencies, such as liquid, cream, solid/cake and powder forms. The factor that affects the physical stability of the cream blush is the viscosity or thickness. Beeswax (cera alba) is one of the ingredients that can increase the viscosity and has a function as a thickener or stiffening. This study aims to determine the optimal concentration of beeswax in red dragon (H.costaricensis) fruit extract cream blush formulations that meet the physical quality standards comparable to similar commercial products. The study was conducted by varying beeswax concentrations in three formulations (FI, FII, and FIII) of red dragon fruit extract cream blush at 10%, 15%, and 20%, respectively. The physical quality tests included organoleptic tests, homogeneity, pH, and spreadability, which were compared with those of commercial cream blush products. Based on the physical quality evaluation, all three formulations showed good physical properties. However, among the tested formulations, FI (10% beeswax) exhibited the closest physical quality characteristics to commercial blush product.